Classification of a frameshift/extended and a stop mutation in WT1 as gain-of-function mutations that activate cell cycle genes and promote Wilms tumour cell proliferation. (11th March 2014) - Busch, Maike; Schwindt, Heinrich; Brandt, Artur; Beier, Manfred; Görldt, Nicole; Romaniuk, Paul; Toska, Eneda; Roberts, Stefan; Royer, Hans-Dieter; Royer-Pokora, Brigitte
Abstract : The WT1 gene encodes a zinc finger transcription factor important for normal kidney development. WT1 is a suppressor for Wilms tumour development and an oncogene for diverse malignant tumours. We recently established cell lines from primary Wilms tumours with different WT1 mutations. To investigate the function of mutant WT1 proteins, we performed WT1 knockdown experiments in cell lines with a frameshift/extension (p.V432fsX87 = Wilms3) and a stop mutation (p.P362X = Wilms2) of WT1, followed by genome-wide gene expression analysis. We also expressed wild-type and mutant WT1 proteins in human mesenchymal stem cells and established gene expression profiles. A detailed analysis of gene expression data enabled us to classify the WT1 mutations as gain-of-function mutations. The mutant WT1 Wilms2 and WT1 Wilms3 proteins acquired an ability to modulate the expression of a highly significant number of genes from the G2/M phase of the cell cycle, and WT1 knockdown experiments showed that they are required for Wilms tumour cell proliferation. p53 negatively regulates the activity of a large number of these genes that are also part of a core proliferation cluster in diverse human cancers. Our data strongly suggest that mutant WT1 proteins facilitate expression of these cell cycle genes by antagonizing transcriptional repression mediated by p53. We show that mutant WT1 can physically interact with p53. Together the findings show for the first time that mutant WT1 proteins have a gain-of-function and act as oncogenes for Wilms tumour development by regulating Wilms tumour cell proliferation.